2018
DOI: 10.1002/clc.22955
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of multiple therapeutic targets for cardiovascular disease prevention: Retrospective analysis of real practice in Italy

Abstract: Background Pharmacological therapy in patients at high cardiovascular (CV) risk should be tailored to achieve recommended therapeutic targets. Hypothesis To evaluate individual global CV risk profile and to estimate the control rates of multiple therapeutic targets for in adult outpatients followed in real practice in Italy. Methods Data extracted from a cross‐sectional, national medical database of adult outpatients in real practice in Italy were analyzed for global CV risk assessment and rates of control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(27 reference statements)
0
7
1
1
Order By: Relevance
“…We also used a stricter LDL cholesterol target of < 1.8 mmol/L (70 mg/dL) but a looser HbA1c target of < 64 mmol/mol (8%) for those with ASCVD. While we did not show differences in target control rates for patients with versus patients without prior CVD, others have noted high risk status to be associated with poorer achievement of targets for BP, lipids and obesity . Also, in a large multicentre survey of 4056 adults with DM in a primary care setting in Beijing, China, only 11% were noted to be at goals for LDL cholesterol, BP and fasting glucose, which is not substantially different from the 53 mmol/mol (7%) we reported in our earlier pooled cohort of US patients with DM …”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We also used a stricter LDL cholesterol target of < 1.8 mmol/L (70 mg/dL) but a looser HbA1c target of < 64 mmol/mol (8%) for those with ASCVD. While we did not show differences in target control rates for patients with versus patients without prior CVD, others have noted high risk status to be associated with poorer achievement of targets for BP, lipids and obesity . Also, in a large multicentre survey of 4056 adults with DM in a primary care setting in Beijing, China, only 11% were noted to be at goals for LDL cholesterol, BP and fasting glucose, which is not substantially different from the 53 mmol/mol (7%) we reported in our earlier pooled cohort of US patients with DM …”
Section: Discussioncontrasting
confidence: 90%
“…While we did not show differences in target control rates for patients with versus patients without prior CVD, others have noted high risk status to be associated with poorer achievement of targets for BP, lipids and obesity. 15 Also, in a large multicentre survey of 4056 adults with DM in a primary care setting in Beijing, China, only 11% were noted to be at goals for LDL cholesterol, BP and fasting glucose, 16 which is not substantially different from the 53 mmol/mol (7%) we reported in our earlier pooled cohort of US patients with DM. 5 The somewhat poorer risk factor control we demonstrate in women compared to men with DM is concerning, given that the presence of DM attenuates the pre-menopausal female advantage generally noted for cardiovascular risk.…”
Section: Discussionmentioning
confidence: 54%
“…Especially low control rates were found for LDL-C (4.5%) and body weight parameters (15%). Numerous observational studies, including previous EUROASPIRE surveys, concluded that control of multiple cardiovascular risk factors is poor in clinical practice [20,[23][24][25][26][27], and it is even more difficult to achieve the targets in the primary prevention setting than in coronary patients [20]. In the primary care arm of EUROASPIRE IV, less than half (43%) of the treated patients reached the blood pressure target, one-third (33%) of patients achieved the LDL-C target of <2.5 mmol/L and less than two-thirds (59%) achieved the HbA1c target of <7.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Only a quarter of patients achieved a satisfactory BMI and waist circumference [24]. A retrospective Italian study found a poor control of major cardiovascular risk factors (diastolic blood pressure, LDL-C, HDL-C, triglycerides and BMI) in outpatients with high or very high SCORE risks, despite the greater use of pharmacological treatment and lifestyle recommendations [26]. In a cohort of male workers with no previous CVD, only 46% of the workers with hypertension, 22% of those with diabetes and 11% of those with dyslipidemia were controlled [23].…”
Section: Discussionmentioning
confidence: 99%
“…Автори роблять висновок про те, що особи з ви-соким та дуже високим рівнем серцево-судинно-го ризику за SCORE в Італії не досягли рекомен-дованих терапевтичних цілей в умовах реальної клінічної прак тики [27].…”
Section: обговоренняunclassified